The Condyloma acuminata - the review of the treatment methods - Słowik, Magdalena; Gierlach, Katarzyna; Nowak, Karolina; Nowak, Karolina; Drygała, Zuzanna; Zielińska, Zuzanna; Wyrwał, Julia; Olejarz, Zuzanna; Krasuska, Martyna; Nieć, Maria (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Condyloma acuminata, a benign manifestation of HPV infection, is a common sexually transmitted disease. Condyloma acuminata most commonly affects the anogenital area, but can also occur in the oral cavity. Macroscopically the lesions present as raised, fleshy papules, sometimes flat and broad, pedicled or cauliflower-like. Generally, the lesions are multiple, and as they grow, tend to coalesce into larger ones. Due to the lack of symptoms, condyloma acuminata are often found incidentally during routine medical appointments, e.g. in gynecologist’s offices. Additional symptoms and signs are pain, minor bleeding and pruritus. Patients suffering from condyloma acuminata are often in psychological and psychosexual distress. This work aims to provide a summary of the currently available treatment options based on scientific reports to date. A brief description of the state of knowledge: Among the factors that increase the risk of the HPV infection are age, lifestyle, promiscuity, smoking, HIV infection, a history of chlamydia or gonorrhea infections. To date, no treatment algorithm has been developed for condyloma acuminata. Two vaccines are on offer as primary prevention, Gardasil and Cervarix. The available treatment options are divided into two main groups: patient-administered and physician administered. Surgical methods have the highest therapeutic efficacy. Condyloma acuminata has a high recurrence rate. Usually, a multi-session combination treatment is needed to reach total remission. Summary (conclusions): The treatment of condyloma acuminata includes personalized targets due to their diverse clinical picture and the limitations of certain patient groups. The available treatment options do not exhaust the needs of patients suffering from condyloma acuminata. Further research into the effectiveness of specific treatments is advisable.